Viral Membrane Proteins: Structure, Function, and Drug Design - Fischer, Wolfgang B. (Protein Reviews, 2005)
Protein Reviews, a new book series from Springer, covers all aspects of protein investigations including protein chemistry, sequence, 3-D structure, biological activity, proteomics, methodology, and many more new and emerging topics. Volume 1: Viral Membrane Proteins: Structure, Function and Drug Design Edited by Wolfgang B. Fischer This volume, written by renowned leaders in the field, summarizes the current structural and functional knowledge of membrane proteins encoded by viruses while addressing questions about the proteins as potential drug targets. Early praise for this volume: "We all know that you can't treat viral disease with drugs.....That was what all physicians and scientists were taught for decades with conviction but without enough experiments. Fortunately, we were taught wrong: rationally designed drugs are available that work well against influenza as Garman and Laver describe so well (with the help of Wen Yang Wu) in a fascinating chapter of this book. In fact, viral membrane proteins have a range of functions of great medical and biological importance, not so surprisingly if one understands that membrane proteins control a wide range of function because they are gatekeepers for cells. Membrane proteins control entry into cells and viruses. Viral Membrane Proteins" is a wonderful description of some of these proteins. The authors and editor are to be congratulated on producing much more than a collection of reviews and essays. This book can help teach everyone that it is possible to treat viral disease with drugs that bind to membrane proteins. Knowing that, we can hope that more resources will be focused on finding other such drugs to the remaining scourges of mankind, at least those we do not produce ourselves." - Robert S. Eisenberg, Rush University Medical Center, Chicago, IL < .